REDUCING THE NUMBER OF SMOKING THROUGH HEALTH EDUCATION AND SEFT THERAPY IN THE PADUKUHAN KARANGSARI - Fajarina Lathu Asmarani; Endang Nurul Syafitri; Ametkabal K. Luturmas (Jurnal Keperawatan Respati Yogyakarta, 2023)
There is a tendency to start smoking at a younger age. The number of teenage smokers in the world is 30%. In Indonesia, smokers aged 10-18 are 9.1%. In Yogyakarta, 1129 male students were smokers. Karangsari Padukuhan shows 27.5% of teenagers smoking. There is a lot of evidence that shows the bad effects of smoking so that it requires intervention. Interventions that can be given are to provide health education about the dangers of smoking and SEFT therapy. This research method is quasy experimental quantitative research. This research was conducted in Karangsari Elementary School. The data collection time is October, 2022. The sample in this study was selected from an affordable population using the purposive sampling method. The number of samples studied in this study was 30 adolescents. The measuring instrument uses the questionnaire. Data analysis using Wilcoxon. The average number of cigarettes per day is 4.3. After giving the intervention showed 3.43. The value of α shows 0.000, which means that there is an effect of providing health education about the dangers of smoking and SEFT therapy with the number of cigarettes daily. The conclusion of this study is that health education and SEFT therapy are scientifically proven to reduce the number of cigarettes